Analgesia, Sedation, and Neuromuscular Blockade in Infants with Congenital Diaphragmatic Hernia - Weems, Mark F.; Grover, Theresa R.; Seabrook, Ruth; DiGeronimo, Robert; Gien, Jason; Keene, Sarah; Rintoul, Natalie; Daniel, John M.; Johnson, Yvette; Guner, Yigit; Zaniletti, Isabella; Murthy, Karna; the Children's Hospitals Neonatal Consortium Congenital Diaphragmatic Hernia Focus Group (American Journal of Perinatology, 2021)
Objective The aim of this study was to describe the use, duration, and intercenter variation of analgesia and sedation in infants with congenital diaphragmatic hernia (CDH).Study Design This is a retrospective analysis of analgesia, sedation, and neuromuscular blockade use in neonates with CDH. Patient data from 2010 to 2016 were abstracted from the Children's Hospitals Neonatal Database and linked to the Pediatric Health Information System. Patients were excluded if they also had non-CDH conditions likely to affect the use of the study medications.Results A total of 1,063 patients were identified, 81% survived, and 30% were treated with extracorporeal membrane oxygenation (ECMO). Opioid (99.8%), sedative (93.4%), and neuromuscular blockade (87.9%) use was common. Frequency of use was higher and duration was longer among CDH patients treated with ECMO. Unadjusted duration of use varied 5.6-fold for benzodiazepines (median: 14 days) and 7.4-fold for opioids (median: 16 days). Risk-adjusted duration of use varied among centers, and prolonged use of both opioids and benzodiazepines ≥5 days was associated with increased mortality (p < 0.001) and longer length of stay (p < 0.001). Use of sedation or neuromuscular blockade prior to or after surgery was each associated with increased mortality (p ≤ 0.01).Conclusion Opioids, sedatives, and neuromuscular blockade were used commonly in infants with CDH with variable duration across centers. Prolonged combined use ≥5 days is associated with mortality.Key Points
Keywords: opioid; benzodiazepine; paralytic; surgery; neonates; pain; CHND; ECMO